Low-Complexity Repetitive Epitopes of Plasmodium falciparum Are Decoys for Humoural Immune Responses - Hou, Nan; Jiang, Ning; Ma, Yu; Zou, Yang; Piao, Xianyu; Liu, Shuai; Chen, Qijun (Frontiers in Immunology, 2020)
Induction of humoural immunity is critical for clinical protection against malaria. More than 100 malaria vaccine candidates have been investigated at different developmental stages, but with limited protection. One of the roadblocks constrains the development of malaria vaccines is the poor immunogenicity of the antigens. The objective of this study was to map the B-cell epitopes of the Plasmodium falciparum erythrocyte invasion-associated antigens with a purpose of understanding humoural responses and protection. We conducted a large-scale screen using overlapping peptide microarrays of 37 proteins from the P. falciparum parasite, most of which are invasion-associated antigens which have been tested in clinical settings as vaccine candidates, with sera from individuals with various infection episodes. Analysis of the epitome of the antigens revealed that the most immunogenic epitopes were predominantly located in the low-complexity regions of the proteins containing repetitive and/or glutamate-rich motifs in different sequence contexts. However, in vitro assay showed the antibodies specific for these epitopes did not show invasion inhibitory effect. These discoveries indicated that the low-complexity regions of the parasite proteins might drive immune responses away from functional domains, which may be an instructive finding for the rational design of vaccine candidates.